The situation of generations on the labour market in Poland - Justyna Wiktorowicz (Economic and Environmental Studies (E&ES), 2018)
A generational shift is perceived as a significant challenge to organisations, especially in the ongoing changes in contemporary labour market. Four generations meet in the workplace now, while until recently one could talk only about two. Given the growing significance of human capital as a substantial factor of economic growth, the knowledge about individual generations is gaining importance. The aim of this article is to assess the position of particular generations on the labour market in Poland. The statistical analysis was carried out using the individual data of Social Diagnosis 2015 and allows for a quantitative assessment of the working situation of employees from different generations. Basic statistical tests to compare the population, as well as the multifactorial analysis of variance were applied.
Keywords: J53; M54; 330; generations; labour market; analysis of variance